Factors Affecting Farmers' Decisions in Following Rice Farming Insurance in Buay Madang Timur Sub- District - Niswatuwarohmah; Munajat; Sari, Yunita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aims to analyze the factors that influence farmers' decisions in participating in rice farming insurance in Buay Madang Timur Sub-District. The type of research used in this study is a quantitative descriptive method. The data analysis used in this study is multiple regression analysis. The results showed that the factors of farming experience, owned land area, number of family members, age of farmers, level of education, role of extension workers, income of rice farming businesses, success of claims, difficulty of registration and claims had a significant effect on farmers' decisions in participating in the Rice Farming Insurance(RFI) program in Buay Madang Timur Sub-District, Ogan Komering Ulu Timur Regency. The factor that most influences farmers' decisions in participating in the Rice Farm Insurance (RFI) program is the role of extension workers with a standard value of the partial regression coefficient of 6,049.